Pengaruh Religiusitas, Gharar, dan Pemborosan terhadap Perilaku Konsumsi Game Online - Triyananda, Adela; Susilo, Edi (Al-Muamalat Jurnal Hukum dan Ekonomi Syariah, 2025)
This study aims to analyze the influence of religiosity, the element of gharar, and wastefulness on online gaming consumption behavior among young users. The research contributes to broadening the understanding of how religious values and Islamic economic principles can serve as a foundation for shaping wise digital consumption behavior. A quantitative approach was employed using a survey method targeting respondents aged 18–25 who actively play online games and have made in-game purchases. Data were collected through a Likert-scale questionnaire and statistically analyzed. The findings indicate that religiosity, awareness of gharar, and understanding of wastefulness have a significant negative effect on online gaming consumption behavior. The higher the level of religiosity and understanding of the principles of gharar and israf, the lower the tendency of individuals to engage in excessive in-game spending.